Developing English Materials for nursing students of SMK Kesehatan Bali Medika Denpasar - ., I GEDE ARIS PRATAMA PUTRA; ., PROF. DR. NI NYOMAN PADMADEWI, M.A.; ., DR. I GEDE BUDASI, M.Ed.DIP APPLIN (Jurnal Pendidikan dan Pembelajaran Matematika Indonesia, 2017)
This study aimed at: a) developing materials for teaching English for nursing students of SMK Kesehatan Bali Medika Denpasar; b) knowing the quality of the developed materials for teaching English for nursing students of SMK Kesehatan Bali Medika Denpasar as perceived by expert judges. This study used R & D model proposed by Sugiyono (2013). Step 1 (identifying the potency & problem phase or need analysis phase) of Sugiyono Model of R&D Design used Hutchinson & Waters?s Learning-Centered Need Analysis Framework (1987) in order to be used to analyze target and learning needs of English for nursing students. The present study was limited into developing the product and expert judgment. Therefore, the field test was not conducted in the present study. The materials were designed by following the model of ESP material design of Hutchinson and Waters (1987:108) which consisted of input, content focus, language focus, and task. The findings of this study showed that there were 8 units of English for nursing students? material had been developed. Those were; (1) Establishing a Relationship; (2) Giving Directions in Hospital; (3) Health Problems; 4) Dimension of Symptoms; 5) Diagnosing Health Problems; 6) Sharing Observation; (7) General Assessment; (8) Patient Assessment. The materials were focused on developing the students? speaking ability. The quality of the product was very good (Product Quality = 4.13) and had met the criteria of material evaluation checklist proposed by McDonough et al (2013).Kata Kunci : materials, students, nursing Penelitian ini bertujuan untuk: (a) mengembangkan materi bahasa inggris keperawatan untuk pengajaran mata pelajaran bahasa inggris keperawatan siswaSMK Kesehatan Bali Medika Denpasar; (b) mengetahui kualitas materi bahasa inggris keperawatan untuk pengajaran mata pelajaran bahasa inggris keperawatan siswa SMK Kesehatan Bali Medika Denpasar dari penilaian para ahli. Penelitian ini dirancang dalam bentuk Penelitian dan Pengembangan model Sugiyono (2013). Tahap pertama Penelititan dan Pengembangan model Sugiyono (tahap mengindentifikasi potensi dan masalah atau analisis kebutuhan) menggunakan model analisis kebutuhan Learning Centered Hutchinson dan Waters (1987) untuk digunakan untuk menganalisa kebutuhan target dan belajar mata kuliah bahasa inggris keperawatan. Penelitian ini hanya terbatas dalam pengembangan produk dan uji pakar. Sehingga penelitian ini tidak diarahkan untuk menguji coba produk di lapangan. Materi ajar didesain mengunakan model Hutchinson dan Waters (1987:108) yang terdiri dari input, content focus, language focus, dan task. Hasil penelitian menunjukkan bahwa terdapat 8 unit materi bahasa inggris keperawatan yang sudah dikembangkan. Materi-materi tersebut adalah: (1) Establishing a Relationship; (2) Giving Directions in Hospital; (3) Health Problems; 4) Dimension of Symptoms; 5) Diagnosing Health Problems; 6) Sharing Observation; (7) General Assessment; (8) Patient Assessment. Materi tersebut difokuskan untuk mengembangkan kemampuan berbicara bahasa inggris siswa. Kualitas produk sangat bagus (kualitas produk = 4.13) dan sudah memenuhi kriteria evaluasi materi McDonough dkk (2013).keyword : materi, mahasiswa, keperawatan